Monitoramento e identidade linguística : um estudo de palavrões em duas versões de uma obra literária itabaianense - Menezes, Keila Vasconcelos (2022)
Swear words are linguistic marks that are subject to strong social stigma. We know that the same speaker monitors his linguistic uses depending on his interlocutor (BELL, 1984), and in our study, we sought to understand how this linguistic monitoring takes place, by an author, in relation to the use of profanity to build personas in his work. In “Feijão de Cego”, by Vladimir Souza Carvalho, from Sergipe, born in Itabaiana, judge, historian, poet, folklorist and writer, profanity is a frequent linguistic feature. In this way, we seek to observe the linguistic monitoring in a literary work, and how the author manipulates linguistic marks that are the target of strong social stigma, in order to answer the following question: What are the effects of linguistic monitoring in the use of profanity for the construction of identities and social personas in “Feijão de Cego”? For this research, in addition to the published and single-edition version, we had access to the handwritten version, granted by the author, which allowed us to observe the linguistic monitoring based on the comparison of the profanity present in the two versions of the work, following the criterion of frequency , and the correlation of such linguistic marks to the social aspects evidenced by the literary text. This study is of a qualitative and quantitative nature and is in line with the perspective of sociolinguistic analysis, more specifically in studies that observe style as a social construction, and focuses on the concepts of Eckert (1992, 2008, 2012), who proposes the style of the persona as the most expressive factor to understand the meaning of variation and communities of practice as a starting point for the analysis of stylistic variation. Since the personas in “Feijão de Cego” are built through the perspective of an author from Itabaiana and there are eleven stories whose narrative space is located in the city of Itabaiana-SE, in addition to having access to studies that deal with typical profanity associated with the repertoire of this community (FREITAG, SANTOS, SANTOS, 2009; SOARES, 2011) and socially constructed images of Itabaiana and its residents (MENEZES, W.O., 2010; SANTANA, MARIANO, 2013; MENESES, 2015; CUNHA, MARIANO, 2017; MENEZES, 2018), we took Itabaiana as a starting point and sought to identify whether there are specific lexicon and social images that characterize the Itabaiana personas of the work to the detriment of the other tales, located in other Sergipe cities. The results point to the construction of a sergipe identity, mainly from the countryside, in the studied work, with no specific social or linguistic aspects that differentiate the tales from itabaiana from the others. In the published version of the work, compared to the handwritten version, there is an attenuation of this local identity through a significant decrease in the frequency of more regional profanity, such as “peste” and “cabrunco”. In addition, the reduction and/or removal of heavier swear words, such as “puta”, replacing them with less stigmatized terms (“safada”, “cachorra”), demonstrates the effects of linguistic monitoring that act not only in speech, but also in literary writing.